PENGARUH WAKTU PEMBENTUKAN DAN KESTABILAN HIDRINDANTIN SERTA KONSENTRASI NINHIDRIN PADA PEMBUATAN TES KIT SIANIDA - Sulistyarti, Hermin; Atikah, Atikah; Zulfah, Novy Lailatuz (Jurnal Ilmu Kimia Universitas Brawijaya, 2015)
Cyanide is a compound which has a potential to harm human health even causes to death. The existing methods for cyanide analysis can’t be done by all societies because they require certain expertise, expensive, and time consuming.  Alternative method in the form of a test kit has been developed for cyanide determination by the formation of a blue hydrindantin in the presence of ninhydrin. The performance of test kit were optimized towards the time of formation and stability hydrindantin as well as the concentration of ninhydrin. Optimization was done by measuring the absorbance using Spectronic-20 at maximum wavelength of 590 nm under alkaline condition (pH 12). The blue hydrindantin was formed spontaneously and stable for 0-30 minutes. After 30 minutes, color of hydrindantin was faded. Thus, 5 minutes was chosen as optimum time suits to measure cyanide using this test kit. Ninhydrin concentration studied was 0.5-3.5 % (w/v), and  performed optimum absorbance of hydrindantin at 1.0 %. Under the optimum time and ninhydrin of concentration, the cyanide test kit standard color can be used to determine cyanide at the concentration range of 0.5-6.0 ppm because the color of hydrindantin at concentration range of cyanide 7.0-10.0 ppm was indistinguishable. Key words: Hydrindantin, ninhydrin, optimization,  cyanide, test kit.